2004
DOI: 10.1038/432689a
|View full text |Cite
|
Sign up to set email alerts
|

Creating a dry variety of quicksand

Abstract: Sand can normally support a weight by relying on internal force chains. Here we weaken this force-chain structure in very fine sand by allowing air to flow through it: we find that the sand can then no longer support weight, even when the air is turned off and the bed has settled--a ball sinks into the sand to a depth of about five diameters. The final depth of the ball scales linearly with its mass and, above a threshold mass, a jet is formed that shoots sand violently into the air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
140
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(153 citation statements)
references
References 11 publications
10
140
0
Order By: Relevance
“…As in ref. 9, for 4-cm-diameter spheres of varying mass released from rest at the surface of a bed of 40 μm sand grains, a seems equal to −g plus a Coulomb friction term proportional to depth; however, this is only the limiting behaviour as we find in the main plot that the acceleration at z = 0 increases with impact speed. Third, the absolute final penetration depth, d, is plotted in Fig.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…As in ref. 9, for 4-cm-diameter spheres of varying mass released from rest at the surface of a bed of 40 μm sand grains, a seems equal to −g plus a Coulomb friction term proportional to depth; however, this is only the limiting behaviour as we find in the main plot that the acceleration at z = 0 increases with impact speed. Third, the absolute final penetration depth, d, is plotted in Fig.…”
mentioning
confidence: 62%
“…
Experiments on the low-speed impact of solid objects into granular media have been used both to mimic geophysical events 1-5 and to probe the unusual nature of the granular state of matter [6][7][8][9][10] . Observations have been interpreted in terms of conflicting stopping forces: product of powers of projectile depth and speed 6 ; linear in speed 7 ; constant, proportional to the initial impact speed 8 ; and proportional to depth 9,10 .
…”
mentioning
confidence: 99%
“…The origin of the deeper penetration under normal ambient pressure is found to lie in the extra sand fluidization caused by the air flow induced by the falling ball. When an object impacts on a bed of fine, loose grains, it is quickly engulfed and a surprisingly vigorous jet shoots upward from the surface of the sand [1][2][3][4], similar to what happens in a liquid [5][6][7]. Royer et al [4] found a granular jet created at reduced ambient pressure to be smaller than at atmospheric pressure, highlighting the relevant role that interstitial air plays in systems with very small grains (<100 m) [8][9][10].…”
mentioning
confidence: 99%
“…For the experiments presented here we adapted the setup used in [2,3] to allow for the evacuation of air. It consists of a deep bed ( 40 cm) of sand grains between 20 and 60 m in size and with shapes of equivalent eccentricities between 0.2 and 0.6.…”
mentioning
confidence: 99%
See 1 more Smart Citation